Analysis of the Influence of Air Inlet Parameters on Positive Pressure Respiratory Protection Device with Half-face Mask - ZHAO Xintong; TANG Yichang; SHEN Wenli; GUAN Jianhui (Journal of Harbin University of Science and Technology, 2024)
This article focuses on the study of the flow field inside the breathing chamber of a half-face power supply respiratory protection device. The research method is numerical simulation, and the control variables are used to study the effects of the number and angle of air intakes on the CO2 concentration, airflow velocity, pressure, and CO2 inhalation in the breathing chamber. The simulation analysis of the CO2 concentration field and airflow velocity field in the breathing chamber was carried out, and combined with the CO2 concentration distribution nephogram and airflow velocity curve in the mask under different inlet numbers and angles. It was concluded that under the dual inlet structure, the air inlet was facing the front end of the mask, and the angle within 20 ° - 25 ° could not only meet the safety requirements, but also be conducive to the gas exchange in the breathing chamber. The human body was comfortable to wear providing relevant theoretical basis for optimizing the structure of the half-face mask.